Dependable software engineering : theories, tools, and applications : 4th International Symposium, SETTA 2018, Beijing, China, September 4-6, 2018, Proceedings /: theories, tools, and applications : 4th International Symposium, SETTA 2018, Beijing, China, September 4-6, 2018, Proceedings. (2018) - Unknown
No abstract available